2022
DOI: 10.1007/s12664-021-01209-0
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients with hepatocellular carcinoma: An experience from a tertiary care center in India

Abstract: Background The prevalence of hepatocellular carcinoma (HCC) is increasing worldwide and it is now the third most common cause of cancer-related death. HCC is becoming a major health burden with steadily increasing incidence globally. Methods This is an observational study over a 3-year period in a tertiary care center in India. Three hundred and thirty-nine patients diagnosed to have HCC were included in this study. Patients’ clinical, etiological, radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…This is a disease that affects young adults, confirming the results reported by Nnadi et al [10] in Nigeria (48.16±16.55 years) and Nsondé et al [11] in Gabon (45.02±12.3 years). However, a higher average age is reported by Musunuri et al [12] in India (62.8 years) and Trybus et al [13] in Brazil (61 years). This difference could be explained by the fact that India and Brazil have a more developed health system promoting better access to treatment and, in turn, an increase in patient survival.…”
Section: Discussionmentioning
confidence: 72%
“…This is a disease that affects young adults, confirming the results reported by Nnadi et al [10] in Nigeria (48.16±16.55 years) and Nsondé et al [11] in Gabon (45.02±12.3 years). However, a higher average age is reported by Musunuri et al [12] in India (62.8 years) and Trybus et al [13] in Brazil (61 years). This difference could be explained by the fact that India and Brazil have a more developed health system promoting better access to treatment and, in turn, an increase in patient survival.…”
Section: Discussionmentioning
confidence: 72%
“…Consistently, Bhatti et al 11 reported that the patients' average age was 57.9 ± 10.1 years and males were in the majority with a male-to-female ratio of 2.8:1. On the other hand, in the study of Kumar K et al 11 13 reported that the Child-Pugh group B was the most common, followed by category A in 45.4% and 41% of the individuals, correspondingly. In the study of Choudhry, A et al 14 reported that the child Pugh class B was most common in 40.2% of the cases, followed by class A 39.2% and class 20.6%.…”
Section: Discussionmentioning
confidence: 91%
“…29 Overall, geographical differences which in turn result in variations in prevalence of various etiological risk-factors for HCC might have an impact on their attribution fractions. 30…”
Section: Discussionmentioning
confidence: 99%